Communication resources and tools for facing the challenges of virtual education - Martínez García, Geraldine (2020)
This paper analyzes the transition of the traditional Peruvian educational system to virtual mode, as a contingency measure for the spread of COVID-19. The impact of the implemented strategies is evaluated and the perception they have generated in the main protagonists of the educational process is measured. A series of deficiencies are identified and discussed, it is also reported on the detection of key points for the development of an efficient educational plan for millions of schoolchildren, emphasizing those with the lowest rate of technological accessibility and connectivity.